Factors Affecting the Intention to Use and Electronic Loyalty of Digital Wallet Users in Metropolitan Lima - Grimaldo Arana, Almendra Michelle; Palacios Gallegos, Maria Isabel; Jauregui Arroyo, Ralphi Ricardo; Cajavilca Gonzales, Berenice (LACCEI, 2024)
This study explored the factors that affect the intention to use and electronic loyalty of digital wallet users in Metropolitan Lima, Peru. Using a quantitative approach with a non-experimental and cross-sectional design, data were collected from 208 residents of Metropolitan Lima through a Google questionnaire. The data obtained were analyzed with SPSS statistical software, applying reliability analysis along with normality and hypothesis tests to validate the results. The findings revealed that performance expectancy, effort expectancy, social influence, and facilitating conditions positively affect the intention to use, which, in turn, influences electronic loyalty.